Moving Away from Thinghood in Law: Animals as a New Legal Category? - Margot Michel (Journal of Animal Law, Ethics and One Health)
The question of what legal status animals have has preoccupied the law for centuries. Most legal systems classify animals among objects and as “things”. This has far-reaching implications on how they can be treated. In particular, the question of commercialisation, i.e. (almost) unlimited use, is closely linked to the status of being a thing and thus, also property. In recent years, many European legal systems have taken the first, albeit still rather tentative, steps towards de-reification of animals. What they look like and what they mean in concrete terms, but also what they might mean in the future, is the subject of this article.